Adsorption of Phosphate Ion in Water with Lithium-Intercalated Gibbsite - Sihombing, Riwandi; Krisnandi, Yuni Krisyuningsih; Widya, Rahma; Luthfiyah, Siti Zahrotul; Yunarti, Rika Tri (Makara Journal of Science, 2015)
In order to enhance adsorption capacity of gibbsite (Al(OH)3 as an adsorbent for the adsorption of phosphate in water, gibbsite was modified through lithium-intercalation. The purification method of Tributh and Lagaly was applied prior to intercalation. The Li-Intercalation was prepared by the dispersion of gibbsite into LiCl solution for 24 hours. This intercalation formed an cationic clay with the structure of [LiAl2(OH)6]+ and exchangeable Cl- anions in the gibbsite interlayer. A phosphate adsorption test using Lithium-intercalated gibbsite (LIG) resulted in optimum adsorption occurring at pH 4.5 with an adsorption capacity of 11.198 mg phosphate/g LIG which is equivalent with 1.04 wt% LIG. The adsorption capacity decreased with decreasing amounts of H2PO4-/HPO4- species in the solution. This study showed that LIG has potential as an adsorbent for phosphate in an aqueous solution with pH 4.5–9.5.